2017
DOI: 10.3390/toxins9020069
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Transcriptome Analysis of Penicillium citrinum Cultured with Different Carbon Sources Identifies Genes Involved in Citrinin Biosynthesis

Abstract: Citrinin is a toxic secondary metabolite of Penicillium citrinum and its contamination in many food items has been widely reported. However, research on the citrinin biosynthesis pathway and its regulation mechanism in P. citrinum is rarely reported. In this study, we investigated the effect of different carbon sources on citrinin production by P. citrinum and used transcriptome analysis to study the underlying molecular mechanism. Our results indicated that glucose, used as the sole carbon source, could signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 59 publications
0
17
0
Order By: Relevance
“…Clean reads of each treatment were mapped to reference genes transcriptome generated by total de novo RNA-seq 52 , 53 . The gene expression level was calculated by the value of FPKM (Fragments Per Kilobase of transcript per Million).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Clean reads of each treatment were mapped to reference genes transcriptome generated by total de novo RNA-seq 52 , 53 . The gene expression level was calculated by the value of FPKM (Fragments Per Kilobase of transcript per Million).…”
Section: Methodsmentioning
confidence: 99%
“…The gene expression level was calculated by the value of FPKM (Fragments Per Kilobase of transcript per Million). The differentially expressed genes were annotated using GO and KEGG enrichment analyses according to a method similar to that described by 52 , 53 . The best BLAST hit was used to assess differential gene expression, which was estimated with log 2 fold change.…”
Section: Methodsmentioning
confidence: 99%
“…A gene encoding a specific transcription factor, often located inside the cluster, activates all the genes in each cluster: patL ( P. expansum ) (Ballester et al ., ; Snini et al ., ) and mrl3 / ctnA ( P. citrinum/P. expansum ) (He and Cox, ; Li et al ., ) for patulin and citrinin clusters, respectively. Bioinformatics analysis has shown that the genome of P. expansum contains other identified or predicted clusters of secondary metabolites (Ballester et al ., ; Nielsen et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…Penicillium citrinum is a filamentous fungus within the genus Penicillium. Its widely distributed and can grow in fruits, grains (Houbraken et al 2010) and tea (Dutta et al 2010;Haas et al 2013); it can produce mycotoxin citrinin under certain conditions (Li et al 2017), which has adverse effects on human kidney and immune system (Aiko and Mehta 2013; F€ ollmann et al 2014). The present study reported the complete mitochondrial genome sequence of a P. citrinum isolated from dark tea, providing important information for population genetics, evolution and taxonomy of this fungus.…”
Section: Penicillium Citrinum; Mitochondrial Genome; Next Generation mentioning
confidence: 99%